„Und ob ich schon wanderte im finstern Tal“: Psalm 23 auf dem Hintergrund altorientalischer und alttestamentlicher Todesvorstellungen - Emmendörffer, Michael (Biblische Zeitschrift, 2020)
Focussing on V 4 with its motif of the “darkest valley” (NIB) the dynamics, theological coherence and background motives of Psalm 23 are laid out. Comparison with the newly edited Ancient Near Eastern prayer Sb19319 from second millennium b.c.e. Susa brings several parallel elements to light. Some theses on Old Testament concepts of death conclude the article.